Recycling fibres recovered from composite materials using a fluidised bed process - Kennerley, Jonathan (1998)
This work is concerned with the characterisation and reuse of fibres recovered from end of life thermoset composites by fluidised bed thermal processing. Emphasis is placed on the properties of recovered glass fibres and their reuse in a dough moulding compound and a tissue product.